2011
DOI: 10.1007/s00436-011-2658-z
|View full text |Cite
|
Sign up to set email alerts
|

Babesia ovis as the main causative agent of sheep babesiosis in Iran

Abstract: Babesiosis is a haemoparasitic disease with high economical losses in livestock industry worldwide. The early diagnosis and successful therapy of babesiosis belong to the key steps of control and health management of livestock. Ethanol-fixed blood samples of 400 sheep were analyzed for Babesia infection. Reverse line blot (RLB) was established specifically for Theileria lestoquardi, Theileria (China 1), Theileria (China 2), Theileria ovis, Theileria separata, Babesia ovis, Babesia motasi, Babesia crassa, and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 22 publications
3
33
0
1
Order By: Relevance
“…Several species of Babesia ( B. ovis, Babesia motasi, Babesia crassa and Babesia sp. Xinjiang) have been described in small ruminants; amongst them, B. ovis and B. motasi are believed to be causative agents of babesiosis [25, 30, 35, 41]. …”
Section: Introductionmentioning
confidence: 99%
“…Several species of Babesia ( B. ovis, Babesia motasi, Babesia crassa and Babesia sp. Xinjiang) have been described in small ruminants; amongst them, B. ovis and B. motasi are believed to be causative agents of babesiosis [25, 30, 35, 41]. …”
Section: Introductionmentioning
confidence: 99%
“…The parasites were monitored by microscopic examination of Giemsa-stained thin blood smears, and results were verified by PCR analysis, as described previously (22). The serum samples used for the ELISA were available in our laboratories from previous studies (8,14,23) and were as follows: 15 negative samples, confirmed by microscopy and the IFAT, from experimentally infected lambs prior to infection (negative-control samples); 120 serum samples from the same experimentally infected lambs, at 6,7,8,11,21,30,45, and 75 days postinfection; and 76 serum samples from 38 naturally infected sheep, at the time of clinical infection and 20 to 30 days after treatment, in which the presence of the parasite was confirmed by microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…The disease is endemic in European, African, Asian, and Far Eastern countries (1)(2)(3)(4)(5)(6)(7)(8). Babesia ovis is highly pathogenic and, in serious infections, causes pancytopenia.…”
mentioning
confidence: 99%
“…Several species were described in small ruminants: B. ovis, B. motasi, Babesia foliata, Babesia taylori and B. crassa, and the recently identified Babesia (Lintan) (Guan et al, 2008;Ranjbar-Bahadori et al, 2012). Ovine babesiosis is prevalent in Eastern Asia, Iran, the Mediterranean basin and North Africa (Guan et al, 2009;Liu et al, 2007;Ranjbar-Bahadori et al, 2012;Rjeibi et al, 2014;Sevinc et al, 2013;Uilenberg, 2006;Yeruham et al, 1985). Clinical symptoms of the disease include fever, anemia, loss of appetite, hemoglobinuria, icterus, and death (Yeruham et al, 1998b).…”
Section: Introductionmentioning
confidence: 94%
“…Clinical symptoms of the disease include fever, anemia, loss of appetite, hemoglobinuria, icterus, and death (Yeruham et al, 1998b). The principal vector of B. ovis is the tick species Rhipicephalus bursa, whose distribution spreads from Asia to Africa, across the Mediterranean region (Altay et al, 2008, Ranjbar-Bahadori et al, 2012Yeruham et al, 1985). R. bursa is a two-host tick, feeding on a wide range of hosts, including hares, dogs and humans, in addition to several species of ungulates (Yeruham et al, 1996).…”
Section: Introductionmentioning
confidence: 97%